2017
DOI: 10.1007/s00216-017-0600-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of endogenous inflammation-related lipid mediators in ischemic stroke rats using background subtracting calibration curves by liquid chromatography-tandem mass spectrometry

Abstract: Accurate and reliable quantification of endogenous lipid mediators in complex biological samples is a daunting challenge. In this study, a robust and direct endogenous quantitative method using background subtracting calibration curves by liquid chromatography-tandem mass spectrometry was first developed for the determination of endogenous lipid mediators in ischemic stroke rats. Absolute quantification without surrogate matrix could be achieved by using background subtracting calibration curves, which were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…PGs are crucial bioactive mediators contributing to the process of acute inflammation (Stanimirovic & Satoh, 2000). Our previous study presented a significant increase in PGs in ischemic rats, and found that the levels of PGs in rats with STV-Na treatment could be significantly decreased toward normal levels (Yang et al, 2017). In this work, the level of AA in the model group was significantly increased, whereas the AA level was significantly decreased after the intervention of STV-Na.…”
Section: Changes In Aa Metabolismsupporting
confidence: 51%
“…PGs are crucial bioactive mediators contributing to the process of acute inflammation (Stanimirovic & Satoh, 2000). Our previous study presented a significant increase in PGs in ischemic rats, and found that the levels of PGs in rats with STV-Na treatment could be significantly decreased toward normal levels (Yang et al, 2017). In this work, the level of AA in the model group was significantly increased, whereas the AA level was significantly decreased after the intervention of STV-Na.…”
Section: Changes In Aa Metabolismsupporting
confidence: 51%
“…Sample storage is also critical due to the high oxidative susceptibility of lipid mediators at room temperature or the enzymatic residual activity. Then, samples are usually stored at -80ºC and AEDT to inhibit PLA 2 activity [174] or antioxidants like BHT are added [124,125,175].…”
Section: Sample Preparation Methodologies For Lipid Mediatorsmentioning
confidence: 99%
“…It provides a fast and proficient extraction with greater selectivity, major capacity for concentrating analytes, less solvent spending and reduced sample handling steps. Both methodologies can be combined to maximize the purification of particularly complex samples and reduce matrix effects in the subsequent LC-MS analysis [105,124,125,[183][184][185][186][187]. SPE stage is also critical for some lipid mediators which are highly unstable like hydroperoxy lipids.…”
Section: Sample Preparation Methodologies For Lipid Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LLE shows good recoveries for EETs, HETEs and PGs; however, it exhibited lower recoveries for hydrophilic analytes such as tetranor-PGEM and leukotrienes (LTs) [20]. Various SPE materials and protocols are employed and it is inconclusive which material and protocol is the best for extracting oxylipins from biological matrices [24]. …”
Section: Introductionmentioning
confidence: 99%